2012
DOI: 10.1016/j.jval.2012.03.216
|View full text |Cite
|
Sign up to set email alerts
|

PMS27 The Cost-Effectiveness of Denosumab for the Prevention of Osteoporotic Fractures in the Setting of the United States

Abstract: males, 10% and 7% were children and females respectively. Majority of the males (79%) were between the ages of 15-35 years of age. On an average the direct cost incurred to treat the injured cases (103) was PKR13,000 excluding subsidy of at least PKR53,000. The total cost was PKR66,000 (USD805) and this cost shall be considered as minimum cost. CONCLUSIONS: Motorcycle accidents are incurring huge economic burden on society. The morbidity and mortality can be reduced by legislative action concerning helmet use,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…34 A more comprehensive societal perspective was taken among 4 studies. 31,33,39,42 Five of 8 scenarios taking the societal perspective estimated ICERs <$100 000 per QALY, including 2 scenarios where use of denosumab was found to be cost saving among elderly people older than 75 years in Japan. 39 Other studies utilized the health system perspective, 32,36,40 health care sector perspective, 39 or governmental perspective, 39 representing 45 scenarios.…”
Section: Cost-effectivenessmentioning
confidence: 99%
See 4 more Smart Citations
“…34 A more comprehensive societal perspective was taken among 4 studies. 31,33,39,42 Five of 8 scenarios taking the societal perspective estimated ICERs <$100 000 per QALY, including 2 scenarios where use of denosumab was found to be cost saving among elderly people older than 75 years in Japan. 39 Other studies utilized the health system perspective, 32,36,40 health care sector perspective, 39 or governmental perspective, 39 representing 45 scenarios.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…34,40,41 This relationship was further supported in 4 articles, which found that treatment with denosumab was more cost-effective among high-risk patients, individuals with more hip fractures, and patients with more CRFs. 14,34,38,42 Overall, 13 studies across 65 scenarios examined ICERs with some percentage of patients having fractures, where use of denosumab was found to be cost-effective <$100 000 per QALY gained in 78% of scenarios (n = 51), including 7 scenarios where it was cost saving. 14,29,38,40 In studies in Belgium, Japan, and Spain, use of denosumab was found to be <$50 000 per QALY gained even among individuals with no previous fractures.…”
Section: Cost-effectivenessmentioning
confidence: 99%
See 3 more Smart Citations